Digital Information Resources for Disaster Management of Libraries and Information Centres - Biswas, Bidhan Chandra; Choudhuri, Sabuj Kumar (Bangladesh Journal of Library and Information Science, 2012)
A library may procure contents in various sources and forms to serve their clients, particularly in the higher education and research institutes in the developed world to satisfy their urge for vital contents that inspire indigenous research. Libraries and information centres must take adequate measures to save their collection from natural or man-made hazards. To have a strong disaster management commitment for libraries and information centres, the role of digital information is most important. This paper begins with an understanding of disaster the meaning, types and its groups- and then seeks to identify parameters to design and develop a successful disaster management plan, cited examples with images, provided various sources for digital information to mitigate it. For heralding better tomorrow, a concerted effort is needed in this regard. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.12-21 DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12915